2020
DOI: 10.1080/20445911.2020.1778006
|View full text |Cite
|
Sign up to set email alerts
|

The neurophysiological relationship between number anxiety and the EEG gamma-band

Abstract: The development of math anxiety is thought to originate at a young age, as a form of number anxiety, but has not been investigated extensively. Research has shown greater levels of EEG gamma-band activity are experienced during threat perception and attentional bias. This has been identified in high math anxious individuals when confronted with math-based tasks, buthas not yet been explored for number anxiety specifically. Single-digit numbers and letters were presented to 15 high and 15 low math anxious parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Recent research involving neuroimaging and ERP during numerical tasks have shown that cognitive processing differs between individuals with and without math anxiety, even though they may achieve similar performance outcomes (see [ 51 ]). Furthermore, Batashvili et al [ 52 ] found that individuals with math anxiety experienced a threat-related response just by observing simple numerical stimuli. Therefore, the model of reduced attention to numerical stimuli is consistent with the findings that math anxiety may reduce attention to numerical stimuli, even on basic numerical tasks if there is sufficient anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research involving neuroimaging and ERP during numerical tasks have shown that cognitive processing differs between individuals with and without math anxiety, even though they may achieve similar performance outcomes (see [ 51 ]). Furthermore, Batashvili et al [ 52 ] found that individuals with math anxiety experienced a threat-related response just by observing simple numerical stimuli. Therefore, the model of reduced attention to numerical stimuli is consistent with the findings that math anxiety may reduce attention to numerical stimuli, even on basic numerical tasks if there is sufficient anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…Maths anxiety can be described as the feelings of tension and apprehension when manipulating numbers or completing maths-based tasks (Ashcraft, 2002). There is neurophysiological evidence that self-reported maths anxiety is associated with brain activity in anticipation of doing maths (Lyons & Beilock, 2012), during mathematical problem solving (Young et al 2009), and even when presented with basic numerical information (Batashvili et al 2020). Furthermore, maths anxiety has been linked to physiological reactivity in response to maths of increasing difficulty (Hunt et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Despite normal performance in most thinking and reasoning tasks, mathematics (maths) anxious individuals demonstrate poor attainment when solving maths problems [2] [3] as MA interferes with the cognitive processes required for successful mathematical problem solving. Recent work in this area has identified a neural threat response to maths stimuli when high maths anxious individuals are simply presented with a maths problem [4] or merely numbers [5]. As an emotional rather than intellectual problem, MA places the individual in a cognitively passive state in which they experience panic, depression, helplessness, nervousness and fearfulness [6] and is a particular issue for those whose ability is already poor [7].…”
mentioning
confidence: 99%